Expression of Vascular Endothelial Growth Factor (VEGF) in Macrophages, Fibroblasts, and Endothelial Cells in Pterygium Treated with 5-Fluorouracil - Hoyama, Erika [UNESP]; Hata Viveiros, Magda Massae [UNESP]; Shiratori, Claudia [UNESP]; Oliveira, Deilson Elgui de [UNESP]; Padovani, Carlos Roberto [UNESP]; Selva, Dinesh; Schellini, Silvana Artioli [UNESP] (Informa Healthcare, 2015)
Purpose: To evaluate the VEGF expression in macrophages, fibroblasts, and endothelial cells from pterygium before and after 5-fluorouracil (5-FU) exposure.Methods: 68 excised pterygia (42 primary and 26 recurrent) were studied by immunohistochemistry, to analyze its expression in cells from pterygium and normal conjunctiva. VEGF expression was evaluated before and after a 5-FU subconjunctival injection 15 days prior to surgery.Results: Expression in macrophages was moderate in normal conjunctiva and low to moderate in pterygium tissues. In fibroblasts, it was negative or low in both tissues. Pterygium had a higher proportion of high VEGF expression in endothelial cells compared to normal tissue (p<0.05). 5-FU did not have any influence on expression.Conclusion: VEGF expression in pterygium macrophages, fibroblasts, and endothelial cells was low and similar to that normal in conjunctival tissue. High VEGF expression was found in pterygium endothelial cells compared to normal conjunctiva. 5-FU does not impact VEGF expression.
Keywords: Angiogenesis; Antimitotic; Eye; Neovascularization